Pengaruh Video Youtube Tentang Anemia Terhadap Pengetahuan dan Sikap Remaja Putri - Niken Sabrina Aulia; Raihana Nadra Alkaff; Fajar Ariyanti; Ratri Ciptaningtyas; Wulan Nurullinisa (Journal of Religion and Public Health, 2025)
Anemia is a common health problem among adolescent girls and can lead to decreased productivity and academic performance. One in four teenage girls in Kembangan, West Jakarta suffers from anemia.. Health education through video platforms, such as YouTube, has the potential to be an effective method in improvingknowledge and attitudes related to anemia in adolescents. This study aims to analyze the effect of health education through YouTube videos on the knowledge and attitudes of adolescent girls at SMPN 207 West Jakarta. The research design used was quasi-experimental with pre-test and post-test groups consisting of an experimental group (YouTube videos) and a control group (PowerPoint). The number of respondents was40 adolescent girls in each group, which were selected using simple random sampling technique. Data analysis was conducted using Mann-Whitney and independent t-test. The results showed a significant increase in the knowledge and attitude of adolescent girls in the YouTube video group, with a p value of 0.000 (p < 0.05). This shows that the use of YouTube videos is effective in improving adolescents' understanding and attitude towards anemia compared to conventional methods. In conclusion, education through YouTube video media can be used as an alternative health promotion method that is more interesting and effective in improving literacy.  Keywords: Anemia, Health Intervention, Intervention Media